2014
DOI: 10.1007/s00415-013-7239-x
|View full text |Cite
|
Sign up to set email alerts
|

Fetal growth restriction and birth defects with newer and older antiepileptic drugs during pregnancy

Abstract: The primary aim of this study was to assess the risks of fetal growth restriction and birth defects in children exposed prenatally to newer and older antiepileptic drugs, using an unselected epilepsy cohort. Deliveries recorded in the compulsory Medical Birth Registry of Norway 1999-2011 formed the study population. All 2,600 children exposed to antiepileptic drugs during pregnancy were compared to all 771,412 unexposed children born to women without epilepsy. Children of untreated mothers with epilepsy served… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

15
136
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(160 citation statements)
references
References 39 publications
15
136
2
2
Order By: Relevance
“…Another study had previously reported 1 malformation in 30 infants prenatally exposed to pregabalin monotherapy, a risk no different from their reference. 8 Our study included 477 pregabalinexposed women, of whom 353 were on monotherapy, and was replicated in 174 pregabalin-exposed women in MarketScan (118 on monotherapy). The CIs around the main effect estimates from the 4 studies largely overlap (figure e-2), and the accumulated evidence results in a null RR, which suggests that the posited increase in risk is likely explained by chance in the setting of a small sample size.…”
mentioning
confidence: 99%
“…Another study had previously reported 1 malformation in 30 infants prenatally exposed to pregabalin monotherapy, a risk no different from their reference. 8 Our study included 477 pregabalinexposed women, of whom 353 were on monotherapy, and was replicated in 174 pregabalin-exposed women in MarketScan (118 on monotherapy). The CIs around the main effect estimates from the 4 studies largely overlap (figure e-2), and the accumulated evidence results in a null RR, which suggests that the posited increase in risk is likely explained by chance in the setting of a small sample size.…”
mentioning
confidence: 99%
“…[3][4][5][6][7] In a review of the Medical Birth Registry of Norway from 1999 to 2011, the odds ratio for major congenital malformations in children exposed to any AED in utero was 1.27 (95% confidence interval: 1.02-1.59). 8 Epileptic therapy during pregnancy, therefore, requires balance between the benefits to pregnant women and the associated risks of AEDs upon the developing fetus.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Although human data are scarce, pregabalin is a Category C drug: risks cannot be ruled out, but potential benefits may justify the risks of pregabalin during pregnancy. Suggested teratogenic mechanisms include reproductive toxicity, skeletal malformation, neural deficits, spontaneous abortions, growth retardation, and behavioral abnormalities.…”
mentioning
confidence: 99%